Critérios comportamentais utilizados por técnicos na avaliação do desempenho esportivo de futebolista das categorias de base - Câmara, Hugo César Reis (2009)
Currently one of the major concerns in sports is to identify, select, discover and reveal talents in soccer. As principal reasons is perceived the search direct or indirect for resources for players, clubs, media, sports brands and their sponsors. However, high salaries are an exception and not a rule, because the majority of professional players in Brazil receives 1 minimum salary per month. It is also known that on professional clubs, daily, arriving several players to try to be a professional soccer player, however, the majority of clubs - almost all does not present methodological, systematic and analytical aspects to select promising players. The selective processes ("sieves" or "big sieves") developed by technical observers ( olheiros") summarized in the observation of the sportive performance of a big group of players in a period of few minutes given to each player. In this period the target behavior is the ability with the ball. If promising players are identified on that selection, they are referred to the club for a new observation, which will be conducted by the responsible coach of base category in question. It is understood by base categories, the amateur categories (not professional), to serve as a "base" for the formation of the cast of professional clubs. What are sub-13 (under 13 years), sub-15 (under 15 years), sub-17 (under 17 years) and sub-20 (under 20 years). The absence of common criterias and performance indicators of these professionals may hamper the evaluation of promising players, and be a costly activity for the club. This study proposes to identify, characterize and categorize the criterias and methods of behavioral evaluation, used by coaches of base categories of Rio Grande do Norte (RN) to evaluate the sportive performance of young soccer players, with the purpose of to compare the criterias of evaluation of sportive performance of young soccer players, used by coaches with different time of experience in function. The proposal had 2 pilot studies, the first (June and July, 2007) were interviewed 29 coaches, 17 of category sub-13 and 12 of category sub-17. The data were tabulated and organized into spreadsheets in order to describe, and developed a set of descriptors of behavior. And the second (May and June, 2008), with revisions made based on observations, analysis and descriptions found in the first, were interviewed 14 technical of category sub-15. After the results found in pilots, it was possible to outline the study in question, which had 46 coaches base categories of the RN. And from the results show that the characteristic of greatest importance, according to the interviewees was the behavior, the 2nd most important characteristic considered was the motivation, the 3rd was the ability and the 4th was the physical condition and the last was the affiliation. And by analyzing the results to the methods of evaluation of sportive performance used by coaches, it was noted clearly that most uses only the observation to select young soccer players. Therefore, needs a systematization to the selection of soccer players, since there is complexity in the verification of characteristics and aspects involved with purpose to avoid wrong evaluations and selections and the results negligible